Sustentabilidade do cultivo de mandioca em comunidades indígenas do Pantanal Brasileiro (Research, Society and Development, 2021)
We aimed with this study to help maximizing cassava production for subsistence in indigenous communities at the Brazilian Pantanal, by introducing minimal changes to the usual indigenous way of cultivation aiming to reduce human labor in weed management in this crop. For that, we tested distinct intercrops and phosphate sources, taking the Babassu Indigenous Village, located in Miranda‑MS, Brazil, as a reference. The experiment involved the intercrop of cassava with pigeon pea (Cajanus cajan), jack‑bean (Canavalia ensiformis) and millet (Pennisetum americanum) and the source of phosphate fertilizer (mycorrhizal inoculants, P2O5 and without fertilization / mycorrhizal inoculum). Soil samples were collected to study the soil seed bank of spontaneous species. We adopted the phytosociological method to assess the absolute level of infestation, its composition density, frequency, dominance and importance value, and diversity coefficients of Simpson and Shannon-Weiner, as well as the Shannon Evenness Proportion (a sustainability coefficient) for all treatments. Areas were also grouped by similarity of plant species. Cultivation of cassava for subsistence in indigenous areas also selects certain spontaneous species, and management should focus in removing mostly by hand those established in the crop row; the damage to the crop may be higher in years of high abiotic stresses. There is no effect of phosphate supply source (P) in the level or composition of spontaneous species. There is clear evidence that the continued cultivation of cassava for subsistence in indigenous areas of the Brazilian Pantanal is sustainable over time, mainly when intercropped with other food species.